Comparative analysis of h.264 and motion-jpeg2000 compression for video telemetry - Hallamasek, K.; Hallamasek, K.; Schwagler, B.; Oxley, Leslie (2012)
The H.264/AVC standard, popular in commercial video recording and distribution, has also been widely adopted for high-definition video compression in Intelligence, Surveillance and Reconnaissance and for Flight Test applications. H.264/AVC is the most modern and bandwidth-efficient compression algorithm specified for video recording in the Digital Recording IRIG Standard 106-11, Chapter 10. This bandwidth efficiency is largely derived from the inter-frame compression component of the standard. Motion JPEG-2000 compression is often considered for cockpit display recording, due to the concern that details in the symbols and graphics suffer excessively from artifacts of inter-frame compression and that critical information might be lost. In this paper, we report on a quantitative comparison of H.264/AVC and Motion JPEG-2000 encoding for HD video telemetry. Actual encoder implementations in video recorder products are used for the comparison. © International Foundation For Telemetering, 2012.